Chronic Venous Disease and Comorbidities. (July 2015) - Matic, P.; Jolic, S.; Tanaskovic, S.; Soldatovic, I.; Katsiki, N.; Isenovic, E.; Radak, Dj.
We report the relations between comorbidities and chronic venous disease. In this cross-sectional study, information was gathered from 1679 Serbian patients. The majority (65.0%) of patients were women. Mild forms of chronic venous disease (clinical, etiologic, anatomic and pathophysiologic [CEAP] classification; C0s-C1) were more frequent in women (11.6%), while severe forms (CEAP C4-C6) were more commonly encountered in men (42.1%). The most frequent comorbidity was emphysema/chronic obstructive pulmonary disease in both groups (74.3% in males and 70.6% in females). For females, diabetes mellitus ( P < .005), arterial hypertension ( P < .000), and skeletal/joint diseases ( P < .042) were more commonly found in the C4 to C6 category. Both males and females, with severe form of chronic venous disease, may benefit from additional screening for comorbidities. Further studies are needed to clarify the nature of association among comorbidities and chronic venous disease.